2008
DOI: 10.1007/s12017-008-8027-0
|View full text |Cite
|
Sign up to set email alerts
|

Central Mechanisms of HPA Axis Regulation by Voluntary Exercise

Abstract: Stress exerts complex effects on the brain and periphery, dependent on the temporal profile and intensity of the stressor. The consequences of a stressful event can also be determined by other characteristics of the stressor, such as whether it is predictable and controllable. While the traditional view has focused primarily on the negative effects of stress on a variety of somatic systems, emerging data support the idea that certain forms of stress can enhance cellular function. Here we review the current lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
159
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(165 citation statements)
references
References 73 publications
2
159
0
4
Order By: Relevance
“…Similarly, daily wheel-running distances 180 in rodents generally increase during the initial 14-21 days, before plateauing around distances (Stranahan et al 2008). In line with these observations, rats with a loss-of-208 function mutation in the Melanocortin 4 receptor, which have an attenuated HPA 209 sensitivity (Ryan, et al 2014), demonstrated lower daily running distances, persistent 210 decreases in caloric intake, and dysregulation of the brain-reward related circuitry 211 compared to wild-type controls during VWR (Obici et al 2015).…”
Section: Voluntary Wheel Running Is a Physiological Stressor 155mentioning
confidence: 97%
See 1 more Smart Citation
“…Similarly, daily wheel-running distances 180 in rodents generally increase during the initial 14-21 days, before plateauing around distances (Stranahan et al 2008). In line with these observations, rats with a loss-of-208 function mutation in the Melanocortin 4 receptor, which have an attenuated HPA 209 sensitivity (Ryan, et al 2014), demonstrated lower daily running distances, persistent 210 decreases in caloric intake, and dysregulation of the brain-reward related circuitry 211 compared to wild-type controls during VWR (Obici et al 2015).…”
Section: Voluntary Wheel Running Is a Physiological Stressor 155mentioning
confidence: 97%
“…2005; Stranahan et al 2008). Thus, as VWR is a threat to homeostasis, it should be 163 considered a physiological stressor, albeit a voluntary and controllable stressor with 164 a distinct temporal profile.…”
Section: Voluntary Wheel Running Is a Physiological Stressor 155mentioning
confidence: 99%
“…The relationship between exercise and HPA activity is complex as it is influenced by duration, type, intensity and chronicity of exercise; characteristics of the stressor used; and characteristics of the population studied (Campeau et al, 2010, Leal-Cerro et al, 2003, Mastorakos et al, 2005, Stranahan et al, 2008. In an animal study, four weeks of swimming exercise was associated with reduced levels of serum corticosterone and depressive behaviours in rats exposed to high levels of glucocorticoids prenatally (Liu et al, 2012a).…”
Section: Exercise and Its Effect On The Hpa Axismentioning
confidence: 99%
“…In support of this notion, Stranahan et al once reported that running-induced elevations in corticosterone levels are prolonged at least in adult male Sprague-Dawley rats. Moreover, there seems to be a positive correlation between basal corticosterone levels and the amount of voluntary wheel running in mice as well as in rats (Stranahan et al 2008). For example, a positive correlation between corticosterone levels and WRA has been reported in house mice (Hsd:ICR strain) selected for high levels of voluntary running over multiple generations.…”
Section: Discussionmentioning
confidence: 98%
“…Despite these beneficial effects of exercise, the precise underlying mechanism is as yet unclear. Some of the recent studies have focused on the hypothalamicpituitary-adrenal (HPA) axis regulation by exercise in rodent species (reviewed in Stranahan et al 2008).…”
Section: Introductionmentioning
confidence: 99%